A study of pharmacists-joint total parenteral nutrition in haematopoietic cell transplantation in accord with diagnosis related groups: A retrospective clinical research - Le Yang; Lu-lu Qiu; Hui-yi Lv; Miao Li (Taylor & Francis Group, 2024)
Background Within Diagnosis Related Groups, based on service capability, efficiency, and quality safety assessment, clinical pharmacists contribute to promoting rational drug utilisation in healthcare institutions. However, a deficiency of pharmacist involvement has been observed in the total parenteral nutrition support to patients following haematopoietic cell transplantation (HCT) within DRGs.Methods This study involved 146 patients who underwent HCT at the Department of Haematology, the Second Affiliated Hospital of Dalian Medical University, spanning from January 2020 to December 2022.Results Patients were allocated equally, with 73 in the control group and 73 in the pharmacist-involved group: baseline characteristics showed no statistics significance, including age, body mass index, nutrition risk screening-2002 score, liver and kidney function, etc. Albumin levels, prealbumin levels were significantly improved after a 7-day TPN support (34.92 ± 4.24 vs 36.25 ± 3.65, P = 0.044; 251.30 ± 95.72 vs 284.73 ± 83.15, P = 0.026). The body weight was increased after a 7-day support and before discharge (58.77 ± 12.47 vs 63.82 ± 11.70, P = 0.013; 57.61 ± 11.85 vs 64.92 ± 11.71, P < 0.001). The length of hospital stay, costs and the rate of re-admissions were significantly shortened (51.10 ± 1.42 vs 46.41 ± 1.86, P = 0.048; 360,162.67 ± 91,831.34 vs 324,070.16 ± 112,315.51, P = 0.035; 61.64% vs 43.84%, P = 0.046).Conclusions Pharmacist-joint TPN support enhances the service efficiency score of medical units, ensuring the fulfilment of orders and rational medication.